Catalysis in the crystal: synchrotron radiation studies with glycogen phosphorylase b. - Hajdu, J; Acharya, K; Stuart, D; McLaughlin, P; Barford, D; Oikonomakos, N; Klein, H; Johnson, L (1987)
Direct observation of the progress of a catalysed reaction in crystals of glycogen phosphorylase b has been made possible through fast crystallographic data collection achieved at the Synchrotron Radiation source at Daresbury, UK. In the best experiments, data to 2.7 A resolution (some 108,300 measurements; 21,200 unique reflections) were measured in 25 min. In a series of time-resolved studies in which the control properties of the enzyme were exploited in order to slow down the reaction, the conversion of heptenitol to heptulose-2-phosphate, the phosphorylysis of maltoheptaose to yield glucose-1-phosphate and the oligosaccharide synthesis reaction involving maltotriose and glucose-1-phosphate have been monitored in the crystal. Changes in electron density in the difference Fourier maps are observed as the reaction proceeds not only at the catalytic site but also the allosteric and glycogen storage sites. Phosphorylase b is present in the crystals in the T state and under these conditions exhibits low affinity for both phosphate and oligosaccharide substrates. There are pronounced conformational changes associated with the formation and binding of the high-affinity dead-end product, heptulose-2-phosphate, which show that movement of an arginine residue, Arg 569, is critical for formation of the substrate-phosphate recognition site. The results are discussed with reference to proposals for the enzymic mechanism of phosphorylase. The feasibility for time-resolved studies on other systems and recent advances in this area utilizing Laue diffraction are also discussed.